PATTERNS OF INTERACTION IN PEER FEEDBACK PROVISION TO THE STUDENTSâ EXPOSITORY WRITINGS - Mufiz, Ali; Fitriati, Sri Wuli; Sukrisno, Alim (English Education Journal, 2017)
This  study  investigated  studentsâ  nature  in  pair  interaction  due  to  its  vital  role  in  learning. Therefore this study was aimed to describe and to explain patterns of interaction in peer feedback, the aspects of writing the students were concerned within peer feedback, influences of pair interactions to the studentsâ writings, and the studentsâ perceptions and attitudes on peer feedback. This study mostly employed qualitative approach and a case study method. The result showed that five patterns emerged in pair interaction i.e. collaborative pairs, dominant/dominant pair, dominant/passive  pairs,  expert/novice  pairs,  and  passive/passive  pair.  However,  feedback provided by collaborative and expert learners contributed to the revision changes of their partnerâs writings so that the development of writing aspects under these two patterns was better. Besides, other  factors which  contributed to the  studentsâ  writings  were  confounding  variables such as studentâs proficiency, writing capability, and teacher feedback. Thus these results endorsed the former studies e.g. Storchâs (2002b) study, Irisâ (2014) study, and Robersonâs (2014) study. Another result  was  that  whole  students  had  good  perceptions  and  good  attitudes  on  peer  feedback provision. However, the bottom line of this study was that collaborative pairs and expert/novice pairs had better second writings.